Oxide particle–dislocation interaction in 9Cr-ODS steel. (December 2016) - Ijiri, Yuta; Oono, N.; Ukai, S.; Ohtsuka, S.; Kaito, T.; Matsukawa, Y
Highlights: We observed the interaction between oxide particles and dislocations in ODS ferritic steel by in-situ TEM tensile experiment. At the interaction type in ODS ferritic steel, the majority(∼90%) is repulsive type. In the in-situ straining experiments, the obstacle strength α of oxide particles was estimated to be no greater than 0.80. we considered that cross-slip system is suitable as interaction mechanism between oxide particles and dislocation in ODS ferritic steel. Abstract: Oxide Dispersion Strengthened (ODS) ferritic/martensitic steels have an excellent high temperature strength primarily due to a dislocation pinning effect of nanometric oxide particles. In the present work, the interaction between oxide particles and dislocations in 9CrODS ferritic steel was investigated by both static TEM observation and in-situ TEM observation under dynamic straining conditions. The primary concerns of those observations were the obstacle strength of oxide particles and the type of interactions: attractive or repulsive. In the static observation, the majority (∼90%) of all interaction geometries was characterized as repulsive type. In the in-situ straining experiments, the obstacle strength α of oxide particles was estimated to be no greater than 0.80. The experimentally-determined obstacle strength is smaller than that of Orowan type impenetrable obstacle, whereas those oxide particles are, in theory, ideally strong obstacles. The gap between predicted and measured obstacle strength is attributable to cross-slip motion of screw dislocations on the oxide particles.